Connections Between Perceived Social Support and the Body Image in the Group of Women With Diastasis Recti Abdominis - Izydorczyk, Bernadetta; Walenista, Wiktoria; Kamionka, Agata; Lizińczyk, Sebastian; Ptak, Magdalena (Frontiers in Psychology, 2021)
Background: The psychological features of the body image and the role of perceived social support for women with diastasis recti abdominis (DRAM) is significant for the treatment of this group of patients, but it is difficult to identify research on this topic. We aimed to search for similarities and differences between postpartum women with DRAM in terms of their psychological features of the body image and perceived social support from the partner, family and friends. Methods: Three hundred forty-five Polish women with DRAM were asked to fill the The Multidimensional Body-Self Relations Questionnaire (MBSRQ), The Multidimensional Scale of Perceived Social Support (MSPSS) and The Drawing Self-Assessment Sheet. Data analysis included the stepwise regression analysis and k-cluster analysis. Results: We identified several predictors in the group of women with DRAM. Social support of partner, family, and friends are the predictors of self-assessment of general body appearance. Social support of family is a predictor of self-assessment of the health of the body. Social support of friends is a predictor of self-esteem of weight and fear of gaining weight. Moreover, three clusters of women with DRAM were found. Type 1—women with DRAM with one child and low self-esteem of the general appearance of the body, low self-esteem of health condition of the body, high self-esteem of weight, and fear of weight gain, and low level of social support; Type 2—women with DRAM with three or more children and low self-esteem of the general appearance of the body, low self-esteem of health condition of the body, high self-esteem of weight and fear of weight gain, and high level of social support; and Type 3—women with DRAM with two children and high self-esteem for the general appearance of the body, high level of self-esteem for health of the body, low self-esteem of weight and fear of weight gain, and high levels of social support. Conclusions: Social support is a predictor of body image in women with DRAM, but there are other factors that influence body acceptance more in this group of women. Furthermore the three clusters featured in the study may help in treating women with DRAM.